toner

JP7631285B2Active Publication Date: 2025-02-18CANON KK
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2022187676
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-02-28
Filing Date
2022-11-24
Publication Date
2025-02-18
Estimated Expiration
2042-11-24

Smart Images

  • Figure 0007631285000006
    Figure 0007631285000006
  • Figure 0007631285000001
    Figure 0007631285000001
  • Figure 0007631285000002
    Figure 0007631285000002
Patent Text Reader

Abstract

To provide a toner that achieves high electrification characteristics, developability, and fluidity at a high level through durable use regardless of a use environment.SOLUTION: A toner has a toner particle and an external additive. The external additive includes hydrotalcite particles containing silica particles and fluorine. Fluorine exists on a cross section of the hydrotalcite particle containing fluorine. When the content of the hydrotalcite particles containing fluorine based on 100 pts.mass of the toner particles is defined as Wh, and the content of the silica particles as Ws, Wh and Ws are within specific ranges. When the total sum of the areas of peaks present within a range of -140 ppm or more and 100 ppm or less of chemical shift obtained by a solid-state 29Si-NMR DD / MAS method of the silica particles is defined as S, the area of a D-unit peak as D, and the area of a Q-unit peak as Q, Wh, Ws, S, D, and Q satisfy specific relationships.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a toner used in a recording method utilizing electrophotography or the like. [Background technology]

[0002] In recent years, copiers and printers are required to be smaller, faster, and have a longer life, as well as to produce stable images without deterioration in image quality under any environment. For example, Patent Document 1 proposes a toner using hydrotalcite particles represented by formula (A) as an external additive in order to impart high chargeability even in a high-temperature and high-humidity environment. Formula (A) M 2+ y M 3+ x (OH)2A n- (x / n) · m H2O (M 2+ represents a divalent metal ion selected from at least Mg, Zn, Ca, Ba, Ni, Sr, Cu, and Fe, and M 3+ represents a trivalent metal ion selected from at least Al, B, Ga, Fe, Co, and In, and A n- At least CO3 2- , O.H. - , Cl - , I - , F - , Br - , SO4 2- , HCO3 - , CH3COO - , NO3 - represents an anion having a valence of n selected from the group consisting of 0 <x≦0.5、x+y=1であり、m≧0である。) [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2000-035692 A Summary of the Invention [Problem to be solved by the invention]

[0004] When hydrotalcite particles are present on the surface of toner particles, they have the opposite polarity to the toner particles, and when the charge decays, they can act as microcarriers to increase the charge. Furthermore, previous studies have shown that the use of hydrotalcite particles containing fluorine suppresses excessive charging of the toner, suppresses charge-up, and makes it possible to make the charge uniform even during long-term continuous use. However, when fluorine-containing hydrotalcite particles are used in combination with silica particles, the silica particles may adhere to the surfaces of the fluorine-containing hydrotalcite particles to form aggregates, which may inhibit the microcarrier effect of the fluorine-containing hydrotalcite particles. The present disclosure provides a toner that achieves high levels of both high chargeability, developability, and fluidity through durable use, regardless of the usage environment. [Means for solving the problem]

[0005] The present disclosure provides a toner having toner particles and an external additive, The external additive contains silica particles and hydrotalcite particles, In a line analysis in a STEM-EDS mapping analysis of the toner, fluorine is present inside the hydrotalcite particles, The hydrotalcite particles are Magnesium and Contains aluminum, a ratio value F / Al of the atomic concentration of fluorine to aluminum in the hydrotalcite particles, which is obtained from main component mapping of the hydrotalcite particles by STEM-EDS mapping analysis of the toner, is 0.02 to 0.60; When the content of the hydrotalcite particles with respect to 100 parts by mass of the toner particles is defined as Wh, the Wh is 0.040 to 1.000 parts by mass, When the content of the silica particles with respect to 100 parts by mass of the toner particles is designated as Ws, Ws is 0.08 to 6.00 parts by mass, The solid of the silica particles 29 When the sum of the areas of the peaks of M units, D units, T units, and Q units present in the chemical shift range of −140 to 100 ppm obtained by Si-NMR DD / MAS method is S, the area of ​​the peak of the D unit present in the range of −25 to −15 ppm is D, and the area of ​​the peak of the Q unit present in the range of −130 to −85 ppm is Q, The Wh, the Ws, the S, the D and the Q satisfy the following formulas (1) to (3): death, 0.05≦D / Q≦0.50 (1) 0.95≦D / (SQ)≦1.00 (2) 0.4≦Ws / Wh≦20.0 (3) a ratio (Mg / Al) of the atomic concentration of magnesium to aluminum in the hydrotalcite particles, which is obtained from main component mapping of the hydrotalcite particles by STEM-EDS mapping analysis of the toner, is 1.5 to 4.0; Regarding toner. Effect of the Invention

[0006] According to the present disclosure, it is possible to provide a toner that achieves high levels of chargeability, developability, and fluidity through durable use regardless of the usage environment. [Brief description of the drawings]

[0007] [Figure 1] Schematic diagram of EDS line analysis in STEM-EDS mapping analysis DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] In the present disclosure, the description of a numerical range such as "XX or more and YY or less" or "XX to YY" means a numerical range including the lower and upper limits, which are the endpoints, unless otherwise specified. When a numerical range is described in stages, the upper and lower limits of each numerical range can be arbitrarily combined.

[0009] First, in the fluorine-containing hydrotalcite particles, fluorine is intercalated between the layers of the hydrotalcite, which makes the charges of the positively charged hydrotalcite particles uniform and suppresses excess charges. However, the charge density on the surface of the hydrotalcite particles increases due to the intercalation of highly electronegative fluorine between the layers. Therefore, when a substance with strong polarization approaches the surface of the hydrotalcite, a strong induced dipole interaction occurs, and the adhesive force becomes strong. Depending on the treatment state of the silica added as an external additive, silica particles adhere to the surface of the hydrotalcite particles containing fluorine to form aggregates, which inhibits the microcarrier effect of the hydrotalcite particles.

[0010] As a result of extensive investigations, the present inventors have found that it is effective to appropriately control the relationship between the contents of the fluorine-containing hydrotalcite particles and the silica particles, and the treatment state of the silica.

[0011] That is, the present disclosure is A toner having toner particles and an external additive, The external additive contains silica particles and hydrotalcite particles, In a line analysis in a STEM-EDS mapping analysis of the toner, fluorine is present inside the hydrotalcite particles, When the content of the hydrotalcite particles with respect to 100 parts by mass of the toner particles is defined as Wh, the Wh is 0.040 to 1.000 parts by mass, When the content of the silica particles with respect to 100 parts by mass of the toner particles is designated as Ws, Ws is 0.08 to 6.00 parts by mass, The solid of the silica particles 29 When the sum of the areas of the peaks of M units, D units, T units, and Q units present in the chemical shift range of −140 to 100 ppm obtained by Si-NMR DD / MAS method is S, the area of ​​the peak of the D unit present in the range of −25 to −15 ppm is D, and the area of ​​the peak of the Q unit present in the range of −130 to −85 ppm is Q, The toner relates to a toner in which the Wh, the Ws, the S, the D and the Q satisfy the following formulas (1) to (3). 0.05≦D / Q≦0.50 (1) 0.95≦D / (SQ)≦1.00 (2) 0.4≦Ws / Wh≦20.0 (3)

[0012] The presence or absence of fluorine in the hydrotalcite particles can be confirmed by STEM-EDS analysis of the toner. In line analysis in the STEM-EDS mapping analysis of the toner, it is necessary that fluorine is present inside the hydrotalcite particles. Fluorine and aluminum are preferably present. The detection of fluorine inside the hydrotalcite particles by this analysis indicates that fluorine is intercalated between the layers of the hydrotalcite particles. The presence of fluorine inside the hydrotalcite particles improves the fluidity of the toner, suppresses poor regulation, and improves solid followability.

[0013] When the content of the hydrotalcite particles relative to 100 parts by mass of the toner particles is Wh, the Wh is 0.040 to 1.000 parts by mass, preferably 0.050 to 0.800 parts by mass, more preferably 0.100 to 0.500 parts by mass, and further preferably 0.100 to 0.400 parts by mass. If the Wh is less than 0.040 parts by mass, the microcarrier effect is not fully exerted, and the charge rise property is likely to be deteriorated, whereas if the Wh is more than 1.000 parts by mass, the toner fluidity is significantly reduced, resulting in poor solid image conformability.

[0014] The surface treatment state of the silica particles is solid 29 It is calculated by the Si-NMR DD / MAS method. In the DD / MAS measurement method, all Si atoms in the measurement sample are observed, so quantitative information about the chemical bonding state of Si atoms in silica particles can be obtained.

[0015] Generally, solid 29In Si-NMR, four types of peaks can be observed for Si atoms in a solid sample: M unit (formula (4)), D unit (formula (5)), T unit (formula (6)), and Q unit (formula (7)). M unit: (R i )(R j )(R k )SiO 1 / 2 Formula (4) D Unit: (R g )(R h )Si(O 1 / 2 )2 formula (5) T unit:R m Si(O 1 / 2 )3 formula (6) Q unit: Si(O 1 / 2 )4 formula (7) R in the formulas (4), (5), and (6) i , R j , R k , R g , R h , R m represents an alkyl group such as a hydrocarbon group having 1 to 6 carbon atoms, a halogen atom, a hydroxyl group, an acetoxy group, an alkoxy group, or the like, bonded to silicon.

[0016] When silica particles are measured by DD / MAS, the Q unit shows a peak corresponding to the Si atom in the silica particles before surface treatment. In the present disclosure, when the silica particles are surface-treated with a surface treatment agent such as silicone oil, the part derived from the surface treatment agent is also called the silica particle. In addition, the silica particles before surface treatment are also called the silica substrate. The M unit, D unit, and T unit show peaks corresponding to the structure of the silica surface treatment agent represented by the above formulas (4) to (6). Both are solid 29 They can be identified by the chemical shift values ​​in the Si-NMR spectrum. Q units appear at chemical shifts of -130 to -85 ppm, T units at -51 to -65 ppm, D units at -25 to -15 ppm, and M units at 10 to 25 ppm, and can be quantified by their integral values.

[0017] Silica Particle Solid 29The sum of the areas of the peaks of M units, D units, T units, and Q units present in the chemical shift range of -140 to 100 ppm obtained by Si-NMR DD / MAS method is defined as S. The area of ​​the peak of the D unit having a peak top in the range of -25 to -15 ppm is defined as D, and the area of ​​the peak of the Q unit having a peak top in the range of -130 to -85 ppm is defined as Q. In this case, S, D, and Q satisfy the following formulas (1) and (2). 0.05≦D / Q≦0.50 (1) 0.95≦D / (SQ)≦1.00 (2)

[0018] The parameter D / Q means the amount of Si atoms constituting the D unit relative to the amount of Si atoms originating from the silica substrate. Since (SQ) is equivalent to the total Si atomic weight of silica minus the amount of Si atoms originating from the silica substrate, D / (SQ) means the amount of Si atoms constituting the D unit relative to the amount of Si atoms originating from the surface treatment agent. If D / Q is less than 0.05, the amount of surface treatment agent relative to the silica substrate is too small to obtain sufficient hydrophobicity, whereas if D / Q is more than 0.50, the amount of surface treatment agent is too large, decreasing the flowability of the silica particles. When D / Q is 0.05 or more and 0.50 or less, the hydrophobicity and flowability of the silica particles can be compatible. D / Q is preferably 0.10 or more and 0.40 or less, more preferably 0.20 or more and 0.35 or less. D / Q can be controlled by adjusting the amount of raw material during the production of the surface-treated silica.

[0019] If D / (SQ) is less than 0.95, the polarization of the surface treatment agent becomes strong, and the adhesion between the silica particles and the hydrotalcite particles containing fluorine is strong, forming aggregates, which inhibits the microcarrier effect. Therefore, the charge rise property after durability is reduced, and blade fusion and regulation failure are likely to occur. D / (SQ) is preferably 0.98 or more and 1.00 or less, more preferably 0.99 or more and 1.00 or less. The larger the D / (SQ), the more Si atoms that make up the D units in the surface treatment agent. Since the Si in the D unit structure has a higher molecular symmetry than the Si atoms in the M and T unit structures, the polarization of the Si-O bond is alleviated, suppressing the adhesion of silica particles to hydrotalcite particles that contain fluorine. D / (SQ) can be controlled by adjusting the amount of raw material used in the production of surface-treated silica.

[0020] In addition, the solidification of silica particles 29 When the area of ​​the peak of the M unit having a peak top in the range of 0 ppm to 30 ppm in the chemical shift obtained by the Si-NMR DD / MAS method is M, M / S is preferably 0.010 or less, more preferably 0.006 or less, and even more preferably 0.002 or less. There is no particular lower limit, but it is preferably 0.000 or more. M / S is particularly preferably 0.000. M / S represents the ratio of the M unit structure to the Si amount of the entire silica particle. When M / S is in the above range, the polarization of silicon and oxygen on the surface of the silica particle is alleviated, and the adhesion of the silica particle to the fluorine-containing hydrotalcite particle is suppressed.

[0021] When the content of silica particles relative to 100 parts by mass of toner particles is Ws, Ws is 0.08 to 6.00 parts by mass. It is preferably 0.10 to 5.50 parts by mass, more preferably 0.20 to 5.00 parts by mass, even more preferably 0.50 to 1.70 parts by mass, and even more preferably 1.00 to 1.50 parts by mass. By having Ws in the above range, it is possible to obtain a toner having excellent fluidity and durability.

[0022] In addition, the ratio (Ws / Wh) of the content Ws of the silica particles to the content Wh of the fluorine-containing hydrotalcite particles must satisfy the following formula (3). 0.4≦Ws / Wh≦20.0 (3) Ws / Wh is preferably 1.0 or more and 10.0 or less, more preferably 4.0 or more and 8.0 or less. If Ws / Wh is less than 0.4, the amount of silica particles relative to the fluorine-containing hydrotalcite particles is small, and the fluidity of the toner is reduced. If Ws / Wh is more than 20.0, the amount of silica particles is too much compared to the fluorine-containing hydrotalcite particles. Therefore, the silica particles inhibit the contact between the fluorine-containing hydrotalcite particles and the toner particles, and the fluorine-containing hydrotalcite particles are easily detached from the toner. This can lead to contamination of components, etc.

[0023] As described above, by combining fluorine-containing hydrotalcite particles with specific silica particles, it is possible to suppress adhesion between the silica particles and the fluorine-containing hydrotalcite particles. Therefore, even during the early to late stages of durability, the fluorine-containing hydrotalcite particles can demonstrate their inherent performance as a microcarrier. As a result, it is believed that high chargeability, developability, and fluidity can be achieved at high levels regardless of the usage environment. Each component constituting the toner and the method for producing the toner will be described in more detail.

[0024] <Binding resin> Preferably, the toner particles contain a binder resin. As the binder resin, the following polymers or resins can be used. The binder resin preferably contains a polyester resin, and more preferably contains an amorphous polyester. For example, homopolymers of styrene and its substitutes such as polystyrene, poly-p-chlorostyrene, and polyvinyltoluene; styrene-p-chlorostyrene copolymers, styrene-vinyltoluene copolymers, styrene-vinylnaphthalene copolymers, styrene-acrylic acid ester copolymers, styrene-methacrylic acid ester copolymers, styrene-α-chloromethyl methacrylate copolymers, styrene-acrylonitrile copolymers, styrene-vinyl methyl ether copolymers, styrene-vinyl ethyl ether copolymers, styrene-vinyl methyl ketone copolymers, and styrene-acrylonitrile-indene copolymers; polyvinyl chloride, phenolic resins, natural resin-modified phenolic resins, natural resin-modified maleic acid resins, acrylic resins, methacrylic resins, polyvinyl acetate, silicone resins, polyester resins, polyurethane resins, polyamide resins, furan resins, epoxy resins, xylene resins, polyvinyl butyral, terpene resins, coumarone-indene resins, and petroleum-based resins can be used.

[0025] The amorphous polyester is a resin having a "polyester structure" in the binder resin chain, and specific examples of components constituting the polyester structure include divalent or higher alcohol monomer components and acid monomer components such as divalent or higher carboxylic acids, divalent or higher carboxylic acid anhydrides, and divalent or higher carboxylic acid esters.

[0026] Examples of the dihydric or higher alcohol monomer component include alkylene oxide adducts of bisphenol A such as polyoxypropylene(2.2)-2,2-bis(4-hydroxyphenyl)propane, polyoxypropylene(3.3)-2,2-bis(4-hydroxyphenyl)propane, polyoxyethylene(2.0)-2,2-bis(4-hydroxyphenyl)propane, polyoxypropylene(2.0)-polyoxyethylene(2.0)-2,2-bis(4-hydroxyphenyl)propane, and polyoxypropylene(6)-2,2-bis(4-hydroxyphenyl)propane; ethylene glycol, diethylene glycol, triethylene glycol, 1,2- Examples of the glycol include propylene glycol, 1,3-propylene glycol, 1,4-cyclohexanedimethanol, dipropylene glycol, polyethylene glycol, polypropylene glycol, polytetramethylene glycol, sorbitol, 1,2,3,6-hexanetetrol, 1,4-sorbitan, pentaerythritol, dipentaerythritol, tripentaerythritol, 1,2,4-butanetriol, 1,2,5-pentanetriol, glycerin, 2-methylpropanetriol, 2-methyl-1,2,4-butanetriol, trimethylolethane, trimethylolpropane, 1,3,5-trihydroxymethylbenzene, and isosorbide. Among these, the alcohol monomer component that is preferably used is an aromatic diol, and the alcohol monomer component that constitutes the polyester resin preferably contains the aromatic diol in a proportion of 80 mol % or more.

[0027] On the other hand, examples of acid monomer components such as divalent or higher carboxylic acids, divalent or higher carboxylic acid anhydrides, and divalent or higher carboxylic acid esters include aromatic dicarboxylic acids or anhydrides thereof, such as phthalic acid, isophthalic acid, and terephthalic acid; alkyl dicarboxylic acids or anhydrides thereof, such as succinic acid, adipic acid, sebacic acid, and azelaic acid; succinic acid or anhydrides thereof substituted with an alkyl group or alkenyl group having 6 to 18 carbon atoms; and unsaturated dicarboxylic acids or anhydrides thereof, such as fumaric acid, maleic acid, and citraconic acid. Among these, preferred acid monomer components are polyvalent carboxylic acids such as terephthalic acid, succinic acid, adipic acid, fumaric acid, trimellitic acid, pyromellitic acid, benzophenonetetracarboxylic acid, and anhydrides thereof.

[0028] The acid value of the polyester resin is preferably from 1 mgKOH / g to 50 mgKOH / g from the viewpoint of the stability of the triboelectric charge. The acid value can be adjusted to the above range by adjusting the type and amount of monomers used in the resin. Specifically, the acid value can be controlled by adjusting the alcohol monomer component ratio / acid monomer component ratio and molecular weight during resin production. In addition, the acid value can be controlled by reacting the terminal alcohol with a polyacid monomer (e.g., trimellitic acid) after ester condensation polymerization. Furthermore, a crystalline polyester can also be used as the binder resin.

[0029] <Coloring agent> The toner particles may contain a colorant. The colorant is not particularly limited, and for example, the following known colorants may be used alone or in combination. Examples of black colorants include carbon black, and black toned colors obtained by using a yellow colorant, a magenta colorant, and a cyan colorant.

[0030] Magenta colored pigments include: CI Pigment Red 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 21, 22, 23, 30, 31, 32, 37, 38, 39, 40, 41, 48:2, 48:3, 48:4, 49, 50, 51, 52, 53, 54, 55, 57:1, 58, 60, 63, 64, 68, 81:1, 83, 87, 88, 89, 90, 112, 114, 122, 123, 146, 147, 150, 163, 184, 202, 206, 207, 209, 238, 269, 282; CI Pigment Violet 19; CI Bat Red 1, 2, 10, 13, 15, 23, 29, 35. Magenta coloring dyes include solvent dyes such as CI Solvent Red 1, 3, 8, 23, 24, 25, 27, 30, 49, 81, 82, 83, 84, 100, 109, 121; CI Disperse Red 9; CI Solvent Violet 8, 13, 14, 21, 27; CI Disperse Violet 1; basic dyes such as CI Basic Red 1, 2, 9, 12, 13, 14, 15, 17, 18, 22, 23, 24, 27, 29, 32, 34, 35, 36, 37, 38, 39, 40; and CI Basic Violet 1, 3, 7, 10, 14, 15, 21, 25, 26, 27, 28.

[0031] Cyan coloring pigments include the following: CI Pigment Blue 2, 3, 15:2, 15:3, 15:4, 16, 17; CI Vat Blue 6; CI Acid Blue 45, copper phthalocyanine pigments having 1 to 5 phthalimidomethyl groups substituted on the phthalocyanine skeleton. Cyan colored dyes include CI Solvent Blue 70. Yellow coloring pigments include the following: CI Pigment Yellow 1, 2, 3, 4, 5, 6, 7, 10, 11, 12, 13, 14, 15, 16, 17, 23, 62, 65, 73, 74, 83, 93, 94, 95, 97, 109, 110, 111, 120, 127, 128, 129, 147, 151, 154, 155, 168, 174, 1 75, 176, 180, 181, 185;CI Bat Yellow 1, 3, 20. Yellow coloring dyes include CI Solvent Yellow 162. The content of the colorant in the toner particles is preferably 3.0% by mass to 15.0% by mass.

[0032] <Release agent> From the viewpoint of separability, the toner particles preferably contain a wax as a release agent. The wax is not particularly limited, but examples thereof include the following. Hydrocarbon waxes such as low molecular weight polyethylene, low molecular weight polypropylene, alkylene copolymers, microcrystalline wax, paraffin wax, and Fischer-Tropsch wax; oxides of hydrocarbon waxes such as oxidized polyethylene wax or block copolymers thereof; waxes whose main component is fatty acid esters such as carnauba wax; and partially or completely deoxidized fatty acid esters such as deoxidized carnauba wax. Further examples include the following: saturated straight-chain fatty acids such as palmitic acid, stearic acid, and montanic acid; unsaturated fatty acids such as brassidic acid, eleostearic acid, and parinaric acid; saturated alcohols such as stearyl alcohol, aralkyl alcohol, behenyl alcohol, carnaubyl alcohol, ceryl alcohol, and melissyl alcohol; polyhydric alcohols such as sorbitol; esters of fatty acids such as palmitic acid, stearic acid, behenic acid, and montanic acid with alcohols such as stearyl alcohol, aralkyl alcohol, behenyl alcohol, carnaubyl alcohol, ceryl alcohol, and melissyl alcohol; fatty acid amides such as linoleic acid amide, oleic acid amide, and lauric acid amide; methylene bisstearic acid amide, ethylene biscapric acid amide, ethylene bislauric acid amide, hexamethylene biphenyl amide, ethylene bisstearic acid amide, ethylene bisstearic acid amide, ethylene bisstearic acid amide, hexamethylene biphenyl ... Saturated fatty acid bisamides such as stearic acid amide; unsaturated fatty acid amides such as ethylene bisoleic acid amide, hexamethylene bisoleic acid amide, N,N' dioleyl adipic acid amide, and N,N' dioleyl sebacic acid amide; aromatic bisamides such as m-xylene bisstearic acid amide and N,N' distearyl isophthalic acid amide; fatty metal salts (commonly known as metal soaps) such as calcium stearate, calcium laurate, zinc stearate, and magnesium stearate; waxes grafted onto aliphatic hydrocarbon waxes using vinyl monomers such as styrene and acrylic acid; partial esters of fatty acids and polyhydric alcohols, such as behenic acid monoglyceride; and methyl ester compounds having hydroxyl groups obtained by hydrogenating vegetable oils and fats.

[0033] Among these releasing agents, from the viewpoint of improving low-temperature fixing property and hot offset resistance, preferred are hydrocarbon waxes such as paraffin wax and Fischer-Tropsch wax, and fatty acid ester waxes such as carnauba wax. The content of the release agent in the toner particles is preferably 3.0% by mass to 15.0% by mass. When the content of the release agent is within this range, it becomes easy to efficiently exhibit hot offset resistance.

[0034] <Charge control agent> The toner particles may contain a charge control agent. There is no particular limitation on the charge control agent, and any known charge control agent may be used. In particular, a charge control agent that has a high charging speed and can stably maintain a constant charge amount is preferred. The charge control agent may be added internally or externally to the toner particles.

[0035] Examples of charge control agents that control toner particles to be negatively charged include the following: Organic metal compounds and chelating compounds include monoazo metal compounds, acetylacetone metal compounds, aromatic oxycarboxylic acids, aromatic dicarboxylic acids, oxycarboxylic acids, and dicarboxylic acid-based metal compounds. Also included are polycarboxylic acids and their metal salts, anhydrides, or esters, and phenol derivatives such as bisphenol. Further examples include urea derivatives, metal-containing salicylic acid compounds, metal-containing naphthoic acid compounds, boron compounds, quaternary ammonium salts, and calixarenes.

[0036] On the other hand, examples of charge control agents that control toner particles to have a positive charge include the following: nigrosine and nigrosine modified with fatty acid metal salts; guanidine compounds; imidazole compounds; quaternary ammonium salts such as tributylbenzylammonium-1-hydroxy-4-naphthosulfonate and tetrabutylammonium tetrafluoroborate, and onium salts such as phosphonium salts analogous thereto, and lake pigments thereof; triphenylmethane dyes and lake pigments thereof (lake agents include phosphotungstic acid, phosphomolybdic acid, phosphotungstomolybdic acid, tannic acid, lauric acid, gallic acid, ferricyanide, ferrocyanide, etc.); metal salts of higher fatty acids; and resin-based charge control agents. These charge control agents can be used alone or in combination of two or more kinds. The content of these charge control agents in the toner particles is preferably 0.01% by mass to 10% by mass.

[0037] <External additives> The toner contains hydrotalcite particles as an external additive. The hydrotalcite particles are generally represented by the following structural formula (A). M 2+ y M 3+ x (OH)2A n- (x / n) mH2O (A) where 0 <x≦0.5、y=1-x、m≧0である。 M 2+ , and M 3+ represent divalent and trivalent metals, respectively. M 2+ is preferably at least one divalent metal ion selected from the group consisting of Mg, Zn, Ca, Ba, Ni, Sr, Cu, and Fe. 3+ is preferably at least one trivalent metal ion selected from the group consisting of Al, B, Ga, Fe, Co, and In. A n- is an n-valent anion, CO3 2- , O.H. - , Cl - , I- , F - , Br - , SO4 2- , HCO3 - , CH3COO - , and NO3 - These may be used alone or in combination.

[0038] The hydrotalcite particles are n- The hydrotalcite particles contain at least F as M. In other words, the hydrotalcite particles contain fluorine. 3+ It is preferable that the M contains at least Al. 2+ It is preferable that the alloy contains at least Mg. Specifically, Mg 8.6 Al4(OH) 25.2 F2CO3·mH2O, Mg 12 Al4(OH) 32 Examples include F2CO3·mH2O. The hydrotalcite particles may be a solid solution containing a plurality of different elements, and may also contain a trace amount of a monovalent metal.

[0039] The hydrotalcite particles preferably further contain aluminum, and more preferably contain magnesium and aluminum. The ratio of the atomic concentration of fluorine to aluminum in the hydrotalcite particles, F / Al (element ratio), obtained from main component mapping of the hydrotalcite particles by STEM-EDS mapping analysis of the toner, is preferably 0.02 to 0.60, more preferably 0.04 to 0.60, and even more preferably 0.04 to 0.30.

[0040] When F / Al is 0.02 or more, the charge-up suppression effect of fluorine is easily obtained. When F / Al is 0.60 or less, the hydrotalcite particles are less likely to be detached from the toner, and the developing performance becomes better through long-term use. F / Al can be controlled by adjusting the concentration of fluorine during the production of hydrotalcite particles.

[0041] The value of the atomic number concentration ratio of magnesium to aluminum in hydrotalcite particles, Mg / Al (element ratio), obtained from the principal component mapping of hydrotalcite particles by STEM-EDS mapping analysis of the toner, is preferably 1.5 to 4.0, and more preferably 1.6 to 3.8. Mg / Al can be controlled by adjusting the amount of raw materials during the production of hydrotalcite.

[0042] When Mg / Al is 1.5 or more, the positive charge of hydrotalcite particles becomes more appropriate due to the influence of Al, the adhesion force between toner particles and hydrotalcite particles becomes good, and the desired microcarrier effect is easily obtained. When Mg / Al is 4.0 or less, the positive charge property of the entire hydrotalcite particles increases, and the ability to impart charge to the toner becomes better.

[0043] Also, it is preferable that the hydrotalcite particles have water in their molecules, and in formula (A), it is more preferably 0.1 < m < 0.6. When m is 0.1 or more, when the toner is charge-up, it is easy to neutralize and stabilize the charge of the toner. When m is 0.6 or less, the resistance increases and the charge property becomes better.

[0044] The number average particle diameter Dh of the primary particles of the hydrotalcite particles is preferably 60 to 1000 nm, more preferably 60 to 800 nm, and even more preferably 200 to 600 nm. When the number average particle diameter Dh is 1000 nm or less, the fluidity of the toner is likely to improve, and the charge property during durability becomes better.

[0045] The hydrotalcite particles may be hydrophobized with a surface treatment agent. As the surface treatment agent, higher fatty acids, coupling agents, esters, and oils such as silicone oil can be used. Among them, higher fatty acids are preferably used, and specific examples thereof include stearic acid, oleic acid, and lauric acid.

[0046] Furthermore, the toner contains silica particles as an external additive. As described above, the silica particles have D / Q and D / (SQ) that satisfy specific ranges. The silica particles are preferably hydrophobized with a surface treatment agent. For example, the silica particles preferably contain silica-based particles and a surface treatment agent on the surface of the silica-based particles. As the silica that serves as the substrate of the silica particles, silica particles obtained by known methods can be used without particular limitation. For example, fumed silica, wet process silica, sol-gel process silica, etc. are representative. In addition, these silicas may be partially or entirely fused silica.

[0047] It is possible to appropriately select and use a suitable one from fumed silica, wet silica, etc., depending on the required characteristics of the individual toner. In particular, fumed silica is excellent in the effect of imparting fluidity, and is suitable as a silica base used in an external additive for electrophotographic toners.

[0048] It is preferable to use silica particles that have been surface-treated with a silica base to impart hydrophobicity and fluidity to the silica base. Examples of the surface treatment method include a method of chemically treating the silica base with a silicon compound that reacts with or physically adsorbs to the silica base.

[0049] Examples of surface treatment agents for silica include silane compounds, silane coupling agents, unmodified silicone oils, various modified silicone oils, and other organic silicon compounds. These treatment agents may be used alone or in combination. Among these, unmodified silicone oil is particularly preferred, and the silicone oil is particularly preferably polydimethylsiloxane composed of D units with low polarization from the viewpoint of adhesion to fluorine-containing hydrotalcite particles. That is, the silica particles are preferably silicone oil-treated silica particles whose surfaces are treated with silicone oil. Generally, from the viewpoint of toner fluidity, silicone oil-treated silica particles are inferior to silica particles treated with HMDS, etc. However, when the toner contains fluorine-containing hydrotalcite particles as an external additive, the adhesive force between the fluorine-containing hydrotalcite particles and the silicone oil-treated silica particles externally added to the toner decreases, and therefore the fluidity of the toner is improved compared to when silica particles treated with HMDS, etc. are externally added, which is preferable.

[0050] The number-average particle diameter Ds of the silica particles is preferably 5 to 100 nm, more preferably 6 to 50 nm, and even more preferably 7 to 40 nm. By externally adding silica particles in this particle diameter range to the toner particles, the toner properties such as the chargeability and fluidity of the toner can be adjusted to obtain good development properties, and the fluidity and chargeability imparted to the toner can be easily secured throughout durability.

[0051] The ratio Dh / Ds of the number average particle diameter Dh (nm) of the fluorine-containing hydrotalcite particles to the number average particle diameter Ds (nm) of the silica particles is preferably 5.0 to 200.0, more preferably 10.0 to 100.0, and even more preferably 13.0 to 60.0. When Dh / Ds is 5.0 or more, the microcarrier effect of the fluorine-containing hydrotalcite particles is more easily exerted, and the charge rise of the toner is further improved. On the other hand, when Dh / Ds is 200.0 or less, the fluidity of the toner is further improved.

[0052] The circularity of the silica particles is preferably less than 0.80, and more preferably from 0.70 to 0.75. When the circularity of the silica particles is less than 0.80, the silica particles are less likely to be detached from the toner, and contamination of components is easily suppressed.

[0053] <Toner manufacturing method> The method for producing the toner particles is not particularly limited, and any known method can be used. For example, a method for producing a toner directly in a hydrophilic medium, such as an emulsion aggregation method, a dissolution suspension method, or a suspension polymerization method, can be used. A pulverization method can also be used, and the toner obtained by the pulverization method can be thermally spheronized. Among them, the toner produced by the emulsion aggregation method is more likely to achieve the effects of the present disclosure, that is, the toner particles are preferably emulsion aggregation toner particles.

[0054] The reason is that the coagulant used in the manufacturing process contains polyvalent metal ions. The presence of these polyvalent metal ions in the binder resin disperses the generated charge inside the toner, making it possible to further stabilize the chargeability of the toner. The polyvalent metal ion is preferably at least one selected from the group consisting of aluminum ions, iron ions, magnesium ions, and calcium ions.

[0055] Hereinafter, a detailed description will be given of a method for producing toner particles by an emulsion aggregation method. (Dispersion liquid preparation process) The binder resin particle dispersion liquid is prepared, for example, as follows: When the binder resin is a homopolymer or copolymer (vinyl resin) of a vinyl monomer, the vinyl monomer is subjected to emulsion polymerization or seed polymerization in an ionic surfactant to prepare a dispersion liquid in which the vinyl resin particles are dispersed in the ionic surfactant. If the binder resin is a resin other than vinyl resin such as polyester resin, the ionic boundary The resin is mixed with an aqueous medium in which a surfactant and a polymer electrolyte are dissolved. Thereafter, this solution is heated to a temperature equal to or higher than the melting point or softening point of the resin to dissolve it, and a dispersion liquid in which the binder resin particles are dispersed in the ionic surfactant is prepared using a dispersing machine with strong shear force such as a homogenizer. The means for dispersion is not particularly limited, and examples thereof include known dispersion devices such as a rotary shear homogenizer, a ball mill having media, a sand mill, and a dyno mill.

[0056] A phase inversion emulsification method may also be used as a method for preparing the dispersion liquid. The phase inversion emulsification method is a method in which a binder resin is dissolved in an organic solvent, a neutralizer and a dispersion stabilizer are added as necessary, and an aqueous solvent is dropped under stirring to obtain emulsified particles, and then the organic solvent in the resin dispersion liquid is removed to obtain an emulsion liquid. In this case, the order of adding the neutralizer and the dispersion stabilizer may be changed. The number-average particle diameter of the binder resin particles is usually 1 μm or less, and preferably 0.01 μm to 1.00 μm. If the number-average particle diameter is 1.00 μm or less, the particle diameter distribution of the final toner is suitable, and the generation of free particles can be suppressed. Furthermore, if the number-average particle diameter is within the above range, uneven distribution between toner particles is reduced, dispersion within the toner is improved, and variations in performance and reliability are reduced.

[0057] In the emulsion aggregation method, a colorant particle dispersion can be used as necessary. The colorant particle dispersion is prepared by dispersing at least colorant particles in a dispersant. The number-average particle diameter of the colorant particles is preferably 0.5 μm or less, more preferably 0.2 μm or less. When the number-average particle diameter is 0.5 μm or less, diffuse reflection of visible light can be prevented, and the binder resin particles and the colorant particles can be easily aggregated in the aggregation process. When the number-average particle diameter is within the above range, uneven distribution between toner particles is reduced, dispersion in the toner is improved, and variations in performance and reliability are reduced.

[0058] In the emulsion aggregation method, a wax particle dispersion can be used as necessary. The wax particle dispersion is prepared by dispersing at least wax particles in a dispersant. The number-average particle diameter of the wax particles is preferably 2.0 μm or less, more preferably 1.0 μm or less. When the number-average particle diameter is 2.0 μm or less, the wax content is less uneven between toner particles, and the image stability over a long period of time is improved. When the number-average particle diameter is within the above range, uneven distribution between toner particles is reduced, dispersion in the toner is improved, and the variation in performance and reliability is reduced. The combination of colorant particles, binder resin particles, and wax particles is not particularly limited and may be freely selected depending on the purpose.

[0059] In addition to the above dispersion, other particle dispersions in which appropriately selected particles are dispersed in a dispersant may be further mixed. The particles contained in the other particle dispersion liquid are not particularly limited and can be appropriately selected depending on the purpose, and examples thereof include internal additive particles, charge control agent particles, inorganic particles, abrasive particles, etc. These particles may be dispersed in the binder resin particle dispersion liquid or the colorant particle dispersion liquid. Examples of dispersants contained in binder resin particle dispersions, colorant particle dispersions, wax microdispersions, and other particle dispersions include aqueous media containing polar surfactants. Examples of aqueous media include water such as distilled water and ion-exchanged water, and alcohols. These may be used alone or in combination of two or more. The content of the polar surfactant cannot be generally specified, and may be appropriately selected depending on the purpose.

[0060] Examples of polar surfactants include sulfate esters, sulfonates, and phosphate esters. Examples of the surfactant include anionic surfactants such as alcohol-based and soap-based surfactants; and cationic surfactants such as amine salt-based and quaternary ammonium salt-based surfactants. Specific examples of anionic surfactants include sodium dodecylbenzenesulfonate, sodium dodecyl sulfate, sodium alkylnaphthalenesulfonate, and sodium dialkylsulfosuccinate. Specific examples of cationic surfactants include alkylbenzene dimethyl ammonium chloride, alkyl trimethyl ammonium chloride, distearyl ammonium chloride, etc. These may be used alone or in combination of two or more. These polar surfactants can also be used in combination with non-polar surfactants, such as polyethylene glycol-based, alkylphenol ethylene oxide adduct-based, polyhydric alcohol-based, and other non-ionic surfactants.

[0061] The content of the colorant particles is preferably 0.1 parts by mass to 30 parts by mass with respect to 100 parts by mass of the binder resin in the aggregated particle dispersion when the aggregated particles are formed. The content of the wax particles is preferably 0.5 to 25 parts by mass, and more preferably 5 to 20 parts by mass, relative to 100 parts by mass of the binder resin in the aggregated particle dispersion when the aggregated particles are formed. Furthermore, in order to more precisely control the chargeability of the resulting toner, charge control particles and binder resin particles may be added after the aggregated particles are formed. The particle sizes of the binder resin particles, colorant particles, and other particles are measured using a laser diffraction / scattering type particle size distribution measuring device LA-960V2 manufactured by Horiba, Ltd.

[0062] (Agglutination process) The aggregation step of forming aggregated particles is a step of forming aggregated particles containing binder resin particles, and, if necessary, colorant particles, wax particles, etc., which are added as necessary, in an aqueous medium containing binder resin particles, and, if necessary, colorant particles, wax particles, etc. The aggregated particles can be formed in an aqueous medium by, for example, adding a pH adjuster, an aggregate agent, and a stabilizer to the aqueous medium and mixing the mixture, and then appropriately applying temperature, mechanical power, and the like. Examples of pH adjusters include alkalis such as ammonia and sodium hydroxide, and acids such as nitric acid and citric acid. Examples of flocculants include monovalent metal salts such as sodium and potassium, divalent metal salts such as calcium and magnesium, trivalent metal salts such as iron and aluminum, and alcohols such as methanol, ethanol, and propanol.

[0063] The stabilizer mainly includes a polar surfactant itself or an aqueous medium containing the same, etc. For example, when the polar surfactant contained in each particle dispersion is anionic, a cationic stabilizer can be selected. The addition and mixing of the flocculant and the like is preferably carried out at a temperature equal to or lower than the glass transition temperature of the resin contained in the aqueous medium. When mixing is carried out under this temperature condition, the flocculation proceeds in a stable state. Mixing can be carried out using, for example, a known mixing device, homogenizer, mixer, etc.

[0064] In addition, in the aggregation process, it is also possible to obtain toner particles having a core / shell structure in which a shell layer is formed on the surface of a core particle by adhering the second binder resin particles to the surface of the aggregated particles using a binder resin particle dispersion liquid containing the second binder resin particles and forming a coating layer (shell layer). The second binder resin particles used in this case may be the same as or different from the binder resin particles constituting the core particles. The aggregation process may be repeated in stages in multiple steps.

[0065] (fusion process) The fusion process is a process in which the obtained aggregated particles are heated and fused. Prior to the fusion process, a pH adjuster, a polar surfactant, a non-polar surfactant, etc. may be appropriately added to prevent fusion between toner particles. The heating temperature may be from the glass transition temperature of the resin contained in the aggregated particles (when there are two or more types of resin, the glass transition temperature of the resin having the highest glass transition temperature) to the decomposition temperature of the resin. Therefore, the heating temperature differs depending on the type of resin of the binder resin particles and cannot be generally specified, but is generally from the glass transition temperature of the resin contained in the aggregated particles to 140° C. or less. The heating can be performed using a heating device or tool known per se. The fusion time is short if the heating temperature is high, and long if the heating temperature is low. In other words, the fusion time depends on the heating temperature and cannot be specified in general, but it is generally between 30 minutes and 10 hours. The toner particles obtained through the above steps can be separated into solid and liquid in accordance with a known method, and the toner particles can be recovered, and then washed, dried, etc. under appropriate conditions. The volume-based median diameter of the toner particles is preferably 3.0 μm or more and 10.0 μm or less.

[0066] (External addition process) Toner particles can be obtained by adding hydrotalcite particles and silica particles to the obtained toner particles. If necessary, other external additives may be added to the extent that the effect of the present disclosure is not impaired.

[0067] The measurement methods for each physical property will be described below. <Method of measuring number average particle size Ds of primary particles of silica particles and number average particle size of primary particles of hydrotalcite particles> A photograph of the toner surface is taken at a magnification of 100,000 times using an FE-SEM S-4800 (manufactured by Hitachi, Ltd.) The magnified photograph is used to measure the particle diameters of 100 or more primary silica particles, and the number-average particle diameter (Ds) of the silica particles is calculated from the arithmetic average. The number average particle size of the hydrotalcite particles is measured using a combination of a scanning electron microscope "S-4800" (product name; manufactured by Hitachi) and elemental analysis by energy dispersive X-ray analysis (EDS). The toner to which external additives have been added is observed, and the hydrotalcite particles are photographed in a field of view magnified up to 200,000 times. From the photographed image, hydrotalcite particles are selected, and the major axis of the primary particles of 100 hydrotalcite particles is measured at random to determine the number average particle size Dh. The observation magnification is adjusted appropriately depending on the size of the external additive. Here, particles that appear as a single grain upon observation are determined to be primary particles. When silica particles or fluorine-containing hydrotalcite particles before external addition are available, they can also be used to calculate the number average particle size by the above method. In addition, when the particle shape is spherical, the absolute maximum length is counted as the particle diameter, and when the particle shape has a major axis and a minor axis, the major axis is counted as the particle diameter. Furthermore, the hydrotalcite particles on the toner surface can be distinguished by the following method.

[0068] <Method for identifying silica particles and hydrotalcite particles> Silica particles and hydrotalcite particles can be identified by a combination of shape observation using a scanning electron microscope (SEM) and elemental analysis using energy dispersive X-ray analysis (EDS). Using a scanning electron microscope "S-4800" (product name; manufactured by Hitachi, Ltd.), the toner is observed in a field of view magnified up to 50,000 times. The focus is set on the surface of the toner particles, and the external additive to be identified is observed. An EDS analysis is performed on the external additive to be identified, and a sequence is determined from the type of element peak. It is possible to identify the silica particles and hydrotalcite particles. When element peaks observed include an element peak of at least one metal selected from the group consisting of Mg, Zn, Ca, Ba, Ni, Sr, Cu, and Fe, which are metals that can constitute hydrotalcite particles, and an element peak of at least one metal selected from the group consisting of Al, B, Ga, Fe, Co, and In, the presence of hydrotalcite particles containing the two types of metals can be inferred. In the case of silica particles, the presence of silica particles can be inferred when element peaks of Si and O are observed. Samples of the hydrotalcite particles and silica particles inferred by the EDS analysis are prepared separately, and shape observation by SEM and EDS analysis are performed. The analysis results of the samples are compared to the analysis results of the particles to be identified to see if they match, and it is determined whether they are hydrotalcite particles and silica particles.

[0069] <Method for measuring element ratios in hydrotalcite particles and method for analyzing fluorine and aluminum inside hydrotalcite particles> The element ratios of hydrotalcite particles are measured by EDS mapping of the toner using a scanning transmission electron microscope (STEM). In EDS mapping measurements, spectrum data is obtained for each pixel in the analysis area. By using a silicon drift detector with a large detection element area, EDS mapping can be measured with high sensitivity. By performing statistical analysis on the spectral data for each pixel obtained by EDS mapping measurement, it is possible to obtain a principal component mapping that extracts pixels with similar spectra, making it possible to map specific components.

[0070] The observation sample is prepared according to the following procedure. 0.5 g of the toner is weighed out, and placed in a cylindrical mold with a diameter of 8 mm and left to stand for 2 minutes under a load of 40 kN using a Newton press to prepare a cylindrical toner pellet with a diameter of 8 mm and a thickness of approximately 1 mm. A 200 nm-thick slice is prepared from the toner pellet using an ultramicrotome (Leica, FC7).

[0071] The STEM-EDS analysis is carried out using the following equipment and conditions. Scanning transmission electron microscope: JEM-2800 manufactured by JEOL Ltd. EDS detector: JED-2300T Dry SD100GV detector (detector area: 100 mm 2 ) EDS analyzer: Thermo Fisher Scientific NORAN System 7 [Conditions for STEM-EDS] STEM accelerating voltage: 200kV ·Magnification: 20,000x Probe size 1nm

[0072] STEM image size: 1024 x 1024 pixels (EDS element mapping images are acquired at the same position.) EDS mapping size: 256 x 256 pixels, Dwell Time: 30 μs, Integration count: 100 frames The ratio of each element in the hydrotalcite particles is calculated based on the multivariate analysis as follows.

[0073] The EDS mapping is obtained by the STEM-EDS analyzer. The collected spectral mapping data is then processed using the measurement command of the NORAN System 7 described above. Multivariate analysis is performed using the COMPASS (PCA) mode in and the principal component map image is extracted. In this case, the setting values ​​are as follows: Kernel size: 3×3 pixels Quantitative map setting: High (slow) Filter Fit Type: High Precision (Slow) At the same time, this operation calculates the area ratio of each extracted principal component in the EDS measurement field of view. Quantitative analysis is performed on the EDS spectrum of each obtained principal component mapping by the Cliff-Lorimer method.

[0074] The toner particle portion and the hydrotalcite particles are distinguished based on the quantitative analysis results of the obtained STEM-EDS main component mapping. The particles can be identified as hydrotalcite particles based on the particle size, shape, content of polyvalent metals such as aluminum and magnesium, and the amount ratio thereof. Furthermore, when fluorine is present inside the hydrotalcite particles, it can be determined by the following means that fluorine is present inside the hydrotalcite particles.

[0075] (Method for analyzing fluorine and aluminum in hydrotalcite particles) Based on the mapping data obtained by the above-mentioned method using STEM-EDS mapping analysis, the fluorine and aluminum in the hydrotalcite particles are analyzed. Specifically, EDS line analysis is performed in the normal direction to the outer periphery of the hydrotalcite particle, and the fluorine and aluminum present inside the particle are analyzed. A schematic diagram of the line analysis is shown in Figure 1(a). For a toner particle 1 and a hydrotalcite particle 3 adjacent to a toner particle 2, a line analysis is performed in the normal direction to the outer periphery of the hydrotalcite particle 3, i.e., in the direction of 5. Note that 4 indicates the boundary of the toner particle. The area in the acquired STEM image where hydrotalcite particles exist is selected using the rectangular selection tool, and line analysis is performed under the following conditions. Line analysis conditions STEM magnification: 800,000x Line length: 200nm Line width: 30nm Number of line divisions: 100 points (intensity measurement every 2 nm)

[0076] When the elemental peak intensity of fluorine or aluminum in the EDS spectrum of the hydrotalcite particle is 1.5 times or more the background intensity, and when the elemental peak intensity of fluorine or aluminum at both ends of the hydrotalcite particle in the line analysis (points a and b in FIG. 1(a)) does not exceed 3.0 times the peak intensity at point c, the element is determined to be contained inside the hydrotalcite particle. Point c is the midpoint of the line segment ab (i.e., the midpoint of the both ends). Examples of X-ray intensities of fluorine and aluminum obtained by line analysis are shown in Figures 1(b) and 1(c). When hydrotalcite particles contain fluorine and aluminum inside, the graph of X-ray intensity normalized by peak intensity shows a shape as shown in Figure 1(b). When hydrotalcite particles contain fluorine derived from a surface treatment agent, the graph of X-ray intensity normalized by peak intensity has peaks near the points a and b at both ends of the fluorine graph, as shown in Figure 1(c). By checking the X-ray intensities derived from fluorine and aluminum in the line analysis, it can be confirmed that the hydrotalcite particles contain fluorine and aluminum inside.

[0077] (Calculation method of the ratio of the atomic concentration of fluorine to aluminum in hydrotalcite particles (element ratio) F / Al) The atomic concentration ratio (element ratio) F / Al of fluorine to aluminum in the hydrotalcite particles obtained from the main component mapping derived from the hydrotalcite particles by the above-mentioned STEM-EDS mapping analysis is obtained in multiple fields of view, and the arithmetic average is taken for 100 or more relevant particles to obtain the atomic concentration ratio (element ratio) F / Al of fluorine to aluminum in the hydrotalcite particles.

[0078] <Calculation method for the ratio of the atomic concentration of magnesium to aluminum in hydrotalcite particles (element ratio) Mg / Al> The same method as for calculating the atomic concentration ratio (element ratio) F / Al of fluorine to aluminum in the hydrotalcite particles described above is carried out for magnesium and aluminum to calculate the atomic concentration ratio (element ratio) Mg / Al of magnesium to aluminum in the hydrotalcite particles.

[0079] <Method for measuring the circularity of silica particles> The circularity of the silica particles is measured by analyzing the toner surface observation image taken with a Hitachi ultra-high resolution field emission scanning electron microscope S-4800 (Hitachi High-Technologies Corporation) using image analysis software ImageJ (developed by Wayne Rashand). The measurement procedure is as follows. (1) Sample preparation Apply a thin layer of conductive paste to a sample stage (aluminum sample stage 15 mm x 6 mm) and apply toner on top of it. Use a blower to blow off excess toner, then allow to dry thoroughly. Set the sample stage in the sample holder. (2) S-4800 observation conditions The observation conditions are as follows. Acceleration voltage: 0.8 kV Emission current: 20μA Detector: [SE up (U)], [+BSE (LA100)] Probe current: [Normal] Focus mode: [UHR] WD: [3.0mm] (3) Image storage Adjust the brightness in ABC mode, take a photo with a size of 640 x 480 pixels, and save it. Use this image file to perform the following analysis. At this time, select a relatively flat part of the toner surface (a field of view where the entire observation surface is in focus) and obtain an image. Adjust the observation magnification appropriately depending on the size of the particles to be observed.

[0080] (4) Image analysis From the obtained SEM observation image, the roundness is calculated using the image processing software ImageJ (developed by Wayne Rashand). The calculation procedure is as follows. [1] Set the scale by selecting [Analyze]-[Set Scale]. [2] Set the threshold value by selecting [Image]-[Adjust]-[Threshold]. (Set the value so that no noise remains and the inorganic particles to be measured remain.) [3] Select the image part of the silica particles to be measured by using [Image]-[Crop]. [4] Overlapping particles can be removed through image editing. [5] [Edit]-[Invert] to invert the black and white image. [6] In [Analyze]-[Set Measurements], check [Area] and [Shape Descriptors]. Also, set [Redirect to] to [None]. Set [Decimal Place(0-9)] to 3. [7] [Analyze]-[Analyze Particle], set the particle area to 0 .0003μm 2 Specify the above and execute. [8] Obtain the circularity value of each particle. [9] Measurements are made on 100 or more observed particles, and the arithmetic mean of the obtained circularity values ​​is calculated to determine the circularity.

[0081] This measurement can also be performed on toner that contains multiple types of fine particles on the surface of the toner particles. When observing the backscattered electron image with the S-4800, it is possible to identify the elements of each particle using the above-mentioned identification method. It is also possible to select particles of the same type based on their shape characteristics. By performing the above measurement on particles of the same type, the circularity of each type of particle can be calculated. The number average particle diameter (Ds, Dh) mentioned above can also be calculated for each type of fine particle in the same way. When silica particles before external additives are available, they can also be used to calculate the circularity by the above method.

[0082] <Silica particle solid 29Calculation method of D / Q and D / (SQ) by Si-NMR DD / MAS measurement> Silica Particle Solid 29 The Si-NMR measurement is performed by separating the silica particles from the toner surface. The following describes the method for separating the silica particles from the toner surface and the solid 29 The Si-NMR measurements are described.

[0083] <Method for separating silica particles from the toner surface> When silica particles separated from the surface of the toner are used as a measurement sample, the silica particles are separated from the toner by the following procedure. Add 1.6 kg of sucrose (Kishida Chemical) to 1 L of ion-exchanged water and dissolve it in a hot water bath to prepare a concentrated sucrose solution. Place 31 g of the concentrated sucrose solution and 6 mL of Contaminon N (a 10% by weight aqueous solution of a neutral detergent for cleaning precision measuring instruments, pH 7, consisting of a nonionic surfactant, an anionic surfactant, and an organic builder, manufactured by Wako Pure Chemical Industries, Ltd.) in a centrifuge tube to prepare a dispersion. Add 10 g of toner to this dispersion, and break up the toner clumps with a spatula or the like. The centrifuge tube is placed in an Iwaki Sangyo KM Shaker (model: V.SX) and shaken for 20 minutes at 350 reciprocations per minute. After shaking, the solution is transferred to a glass tube (50 mL) for a swing rotor and centrifuged at 3,500 rpm for 30 minutes.

[0084] After centrifugation, the toner particles are present in the top layer in the glass tube, and the inorganic fine particle mixture containing silica particles is present in the lower aqueous solution. The upper and lower aqueous solutions are separated and dried, and the toner particles are obtained from the upper layer and the inorganic fine particle mixture is obtained from the lower layer. The above centrifugation process is repeated until the total amount of the inorganic fine particle mixture obtained from the lower layer is 10 g or more.

[0085] Next, 10 g of the obtained inorganic fine particle mixture is dispersed in a dispersion liquid containing 100 mL of ion-exchanged water and 6 mL of Contaminon N. The obtained dispersion liquid is transferred to a glass tube (50 mL) for a swing rotor, and centrifuged in a centrifuge at 3500 rpm for 30 minutes. After centrifugation, the silica particles are present in the top layer of the glass tube, and other inorganic fine particles are present in the aqueous solution in the lower layer. The aqueous solution in the upper layer is collected and centrifuged repeatedly as necessary. After sufficient separation, the dispersion is dried and the silica particles are collected. Next, the solid of the silica particles recovered from the toner particles is 29 The Si-NMR measurement is carried out under the measurement conditions shown below.

[0086] <Solid 29 DD / MAS measurement conditions for Si-NMR measurement> solid 29 The DD / MAS measurement conditions for Si-NMR measurement are as follows: Equipment: JNM-ECX5002 (JEOL RESONANCE) Temperature: room temperature Measurement method: DD / MAS method 29 Si 45° Sample tube: Zirconia 3.2mmφ Sample: Powdered material filled into test tube Sample rotation speed: 10kHz Relaxation delay: 180s Scan:2000

[0087] After the above measurement, the solidification of the silica particles 29 From the Si-NMR spectrum, multiple silane components having different substituents and bonding groups are separated into the following peaks of M units, D units, T units, and Q units by curve fitting. Curve fitting is performed using EXcalibur for Windows (registered trademark) version 4.2 (EX series), software for JNM-EX400 manufactured by JEOL Ltd. Click "1D Pro" from the menu icon to load the measurement data. Next, select "Curve fitting function" from "Command" on the menu bar to perform curve fitting. Curve fitting is performed for each component so that the difference (composite peak difference) between the composite peak obtained by combining the peaks obtained by curve fitting and the peak of the measurement result is minimized. M unit: (R i )(R j )(R k )SiO 1 / 2 Formula (4) D Unit: (R g )(R h )Si(O 1 / 2 )2 formula (5) T unit:R m Si(O 1 / 2 )3 formula (6) Q unit: Si(O 1 / 2 )4 formula (7) (R in the formulas (4), (5), and (6) i , R j , R k , R g , R h , R m represents an alkyl group such as a hydrocarbon group having 1 to 6 carbon atoms, a halogen atom, a hydroxyl group, an acetoxy group, or an alkoxy group bonded to silicon.

[0088] After the peak separation, the integral value of the D unit in the chemical shift range of -25 to -15 ppm and the integral value of the Q unit in the chemical shift range of -130 ppm to -85 ppm are calculated, and the ratio D / Q is calculated. Also, the integral value M of the M unit in the chemical shift range of 10 ppm to 25 ppm is calculated. Also, the sum S of all integral values ​​of the M, D, T, and Q units in the chemical shift range of -140 to 100 ppm is calculated, and D / (SQ) and M / S are calculated.

[0089] <Measurement of the content of silica particles and hydrotalcite particles> The content of silica particles and hydrotalcite particles is calculated from the intensity of metal elements derived from silica particles and hydrotalcite particles using an X-ray fluorescence analyzer (XRF). Using the calibration curve method, the content of silica particles Ws can be calculated from the Si element intensity, and the content of fluorine-containing hydrotalcite particles Wh can be calculated from the intensity of elements identified by STEM-EDS mapping analysis. The measurement procedure is shown below. The measurement equipment used was a wavelength dispersive X-ray fluorescence analyzer "Axios" (PANalytical) and the accompanying software "SuperQ" for setting measurement conditions and analyzing measurement data. ver.4.0F" (PANalytical). Rh is used as the anode of the X-ray tube, the measurement atmosphere is vacuum, and the measurement diameter (collimator mask diameter) is 27 mm. A proportional counter (PC) is used to measure light elements, and a scintillation counter (SC) is used to measure heavy elements.

[0090] The pellets were used to create a calibration curve for determining the silica particle content. - [Product name: Spectro Blend, Ingredients: C 81.0, O 2.9, H 13.5, N 2.6 (mass%), Chemical formula: C 19 H 38 For every 100 parts by mass of the toner powder (ON, shape: powder (44 μm); manufactured by Rigaku Corporation), 0.10 parts by mass of silica particles recovered from the toner are added, and mixed thoroughly using a coffee mill. 4 g of the mixture is placed into a special aluminum ring for pressing and flattened. Using a tablet molding compression machine "BRE-32" (manufactured by Maekawa Test Machinery Manufacturing Co., Ltd.), the mixture is pressed at 20 MPa for 60 seconds to prepare pellets having a thickness of 2 mm and a diameter of 39 mm. Similarly, silica particles are mixed and pelletized to 0.50 parts by mass, 1.00 parts by mass, 5.00 parts by mass, and 10.00 parts by mass, and the count rate (unit: cps) of Si-Kα rays observed at a diffraction angle (2θ) of 109.08° when PET is used as an analyzing crystal is measured, and calculated using the following calibration curve. In this case, the acceleration voltage and current of the X-ray generator are 24 kV and 100 mA, respectively, and the measurement time is 10 seconds. A linear calibration curve is obtained by plotting the obtained X-ray count rate on the ordinate and the silica particle content in each calibration sample on the abscissa. Next, the count rate of the Si-Kα radiation is measured for the toner particles in the same manner, and the content Ws of the silica particles is calculated from the obtained calibration curve. The content Wh of the hydrotalcite particles can also be analyzed and calculated from the intensities of elements identified by the STEM-EDS mapping analysis.

[0091] <Method for measuring the volume-based median diameter of toner> The volumetric median diameter of the toner is calculated as follows. The measurement device used is a precision particle size distribution measurement device using the pore electrical resistance method, "Coulter Counter Multisizer 3" (registered trademark, manufactured by Beckman Coulter, Inc.), equipped with a 100 μm aperture tube. The measurement conditions are set and the measurement data is analyzed using the accompanying dedicated software "Beckman Coulter Multisizer 3 Version 3.51" (manufactured by Beckman Coulter, Inc.). The measurement is performed with an effective measurement channel count of 25,000. The electrolyte solution used for the measurement is prepared by dissolving special grade sodium chloride in ion-exchanged water to a concentration of approximately 1% by mass, for example, "ISOTON II" (manufactured by Beckman Coulter). Before carrying out the measurements and analyses, the dedicated software is set up as follows. In the "Change standard measurement method (SOMME)" screen of the dedicated software, set the total count number in the control mode to 50,000 particles, the number of measurements to 1, and the Kd value to the value obtained using "Standard particle 10.0 μm" (Beckman Coulter). Press the "Threshold / Noise level measurement button" to automatically set the threshold and noise level. In addition, set the current to 1600 μA, the gain to 2, the electrolyte to ISOTON II, and check "Flush aperture tube after measurement." In the "Pulse to particle size conversion setting" screen of the dedicated software, the bin interval is set to logarithmic particle size, the particle size bin is set to 256 particle size bins, and the particle size range is set to 2 μm to 60 μm. The specific measurement method is as follows.

[0092] (1) Pour about 200 mL of the electrolyte solution into a 250 mL round-bottom glass beaker made exclusively for the Multisizer 3, set it on the sample stand, and stir the stirrer rod counterclockwise at 24 revolutions per second. Then, remove dirt and air bubbles from inside the aperture tube using the "Aperture Tube Flush" function of the dedicated software. (2) About 30 mL of the electrolyte solution is placed in a 100 mL flat-bottom glass beaker, and about 0.3 mL of a dilution of "Contaminon N" (a 10% aqueous solution of a pH 7 neutral detergent for cleaning precision measuring instruments, consisting of a nonionic surfactant, an anionic surfactant, and an organic builder, manufactured by Wako Pure Chemical Industries, Ltd.) diluted about three times by mass with ion-exchanged water is added as a dispersant. (3) Two oscillators with an oscillation frequency of 50 kHz are built in with a phase difference of 180 degrees. Prepare an ultrasonic disperser "Ultrasonic Dispersion System Tetra150" (manufactured by Nikkaki Bios Co., Ltd.) with an electric power of 120 W. Place approximately 3.3 L of ion-exchanged water in the water tank of the ultrasonic disperser, and add approximately 2 mL of Contaminon N to this water tank. (4) The beaker (2) is set in the beaker fixing hole of the ultrasonic disperser, and the ultrasonic disperser is operated. Then, the height position of the beaker is adjusted so that the resonance state of the liquid surface of the electrolyte solution in the beaker is maximized. (5) While the electrolyte solution in the beaker in (4) is irradiated with ultrasonic waves, about 10 mg of toner is added little by little to the electrolyte solution and dispersed. Then, ultrasonic dispersion treatment is continued for another 60 seconds. During ultrasonic dispersion, the water temperature in the water tank is appropriately adjusted to be 10°C or higher and 40°C or lower. (6) Using a pipette, the electrolytic solution (5) in which the toner is dispersed is dropped into the round-bottom beaker (1) placed in the sample stand, and the measurement concentration is adjusted to about 5%. Then, measurements are continued until the number of particles measured reaches 50,000. (7) The measurement data is analyzed using the dedicated software provided with the device, and the volume-based median diameter is calculated. EXAMPLES

[0093] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is in no way limited thereto. "Parts" used in the examples are by weight unless otherwise specified.

[0094] <Production Example of Silica Particle 1> Untreated dry silica (BET specific surface area 380 m) was placed in the reaction vessel as the silica substrate. 2 100 parts of silica substrate were sprayed with 30 parts of dimethyl silicone oil (KF-96-50CS manufactured by Shin-Etsu Chemical Co., Ltd.) using a spray nozzle. After spraying, the mixture was stirred for 1 hour while maintaining the above temperature, and a coating treatment was carried out to obtain silica particles 1. The physical properties of silica particles 1 are shown in Table 1.

[0095] <Production Example of Silica Particles 2> Untreated fumed silica with a BET specific surface area of ​​50m 2Silica particles 2 were obtained by carrying out the same treatment as in the production example of silica particles 1, except that the amount of dimethyl silicone oil was 7 parts per grams per gram. The physical properties of silica particles 2 are shown in Table 1.

[0096] <Production Example of Silica Particles 3> Except for changing the amount of dimethyl silicone oil to 45 parts, the same treatment as in the production example of silica particles 1 was carried out to obtain silica particles 3. The physical properties of silica particles 3 are shown in Table 1.

[0097] <Production Example of Silica Particle 4> Untreated fumed silica with a BET specific surface area of ​​200m 2 Silica particles 4 were obtained by carrying out the same treatment as in the production example of silica particles 1, except that the amount of dimethyl silicone oil was 20 parts / g. The physical properties of silica particles 4 are shown in Table 1.

[0098] <Production Example of Silica Particles 5> Except for changing the amount of dimethyl silicone oil to 25 parts, the same treatment as in the production example of silica particles 4 was carried out to obtain silica particles 5. The physical properties of silica particles 5 are shown in Table 1.

[0099] <Production Example of Silica Particles 6> The same treatment as in the manufacturing example of silica particles 4 was carried out, except that the amount of dimethyl silicone oil was changed to 7 parts. Thus, silica particles 6 were obtained. The physical properties of silica particles 6 are shown in Table 1.

[0100] <Production Example of Silica Particle 7> Except for changing the amount of dimethyl silicone oil to 45 parts, the same treatment as in the production example of silica particles 4 was carried out to obtain silica particles 7. The physical properties of silica particles 7 are shown in Table 1.

[0101] <Production Example of Silica Particle 8> Except for using 25 parts of dimethyl silicone oil, the same treatment as in the production example of silica particles 1 was carried out to obtain silica particles 8. The physical properties of silica particles 8 are shown in Table 1.

[0102] <Production Example of Silica Particles 9> Silica particles 9 were obtained by carrying out the same treatment as in the production example of silica particles 4, except that the amount of dimethyl silicone oil was 30 parts. The physical properties of silica particles 9 are shown in Table 1.

[0103] <Production Example of Silica Particles 10> Except for using 40 parts of dimethyl silicone oil, the same treatment as in the production example of silica particles 1 was carried out to obtain silica particles 10. The physical properties of silica particles 10 are shown in Table 1.

[0104] <Production Example of Silica Particle 11> In a 3L glass reactor equipped with a stirrer, a dropping funnel, and a thermometer, 589.6g of methanol, 42.0g of water, and 47.1g of 28% by mass aqueous ammonia were added and mixed. The resulting solution was adjusted to 35°C, and 1100.0g of tetramethoxysilane and 395.2g of 5.4% by mass aqueous ammonia were added simultaneously while stirring. Tetramethoxysilane was added dropwise over 6 hours, and aqueous ammonia was added dropwise over 5 hours. After the dropping was completed, stirring was continued for another 0.5 hours to carry out hydrolysis, and a methanol-water dispersion of hydrophilic spherical sol-gel silica particles was obtained. Next, an ester adapter and a cooling tube were attached to the glass reactor, and the dispersion was thoroughly dried at 80°C under reduced pressure. The obtained sol-gel silica particles were heated in a thermostatic chamber at 400°C for 10 minutes.

[0105] The above process was repeated several times, and the resulting sol-gel silica particles were subjected to a pulverizing treatment using a pulverizer (manufactured by Hosokawa Micron Corporation). The untreated dry silica was converted into sol-gel silica particles obtained by the above procedure, and the same treatment as in the production example of silica particles 1 was carried out, except that dimethyl silicone oil was used in an amount of 15 parts, to obtain silica particles 11. The physical properties of silica particles 11 are shown in Table 1.

[0106] <Production Example of Silica Particles 12> Untreated fumed silica (BET specific surface area 380 m) was placed in the reaction vessel. 2100 parts of the silica substrate were mixed with 20 parts of hexamethyldisilazane (HMDS) as a first surface treatment agent using a spray nozzle. After that, heating and stirring were continued for 1 hour, and then dimethyl silicone oil (manufactured by Shin-Etsu Chemical Co., Ltd.) was added as a second surface treatment agent. The mixture was then heated and stirred for 1 hour in the same manner to obtain silica particles 12. The physical properties of silica particles 12 are shown in Table 1.

[0107] <Production Example of Silica Particles 13> 500 parts of methanol and 70 parts of water adjusted to pH 5.4 with 10% by mass hydrochloric acid were added dropwise and mixed to obtain a catalyst solution. After adjusting the temperature of this catalyst solution to 30°C, 100 parts of tetramethoxysilane and 20 parts of 8.0% by mass ammonia water were simultaneously added dropwise over 60 minutes while stirring to obtain a hydrophilic silica particle dispersion. The obtained silica particle dispersion was then passed through a rotary filter R-Fine (manufactured by Kotobuki Industries Co., Ltd.). ) to a solid content concentration of 40 mass % to obtain a silica dispersion. 50 parts of hexamethyldisilazane (HMDS) as a hydrophobic treatment agent was added to 250 parts of the silica particle dispersion in a reaction vessel, and the mixture was reacted at 130°C for 2 hours, cooled, and then dried by spray drying to obtain silica particles 13. The physical properties of silica particles 13 are shown in Table 1.

[0108] <Production Example of Silica Particles 14> Except for using 55 parts of dimethyl silicone oil, the same treatment as in the production example of silica particles 1 was carried out to obtain silica particles 14. The physical properties of silica particles 14 are shown in Table 1.

[0109] [Table 1] In the table, M, D, T and Q are solids. 29It indicates the ratio of the areas of M units, D units, T units, and Q units when the total S of the ratios of the peak areas of M units, D units, T units, and Q units obtained by Si-NMR DD / MAS method is set to 1.00. Therefore, M / S is the same value as M. Particle size indicates the number average particle size Ds (nm) of primary particles.

[0110] <Preparation of Hydrotalcite Particles 1> A mixed aqueous solution of 1.03 mol / L magnesium chloride and 0.239 mol / L aluminum sulfate (Liquid A), a 0.753 mol / L aqueous solution of sodium carbonate (Liquid B), and a 3.39 mol / L aqueous solution of sodium hydroxide (Liquid C) were prepared. Next, liquid A, liquid B, and liquid C were poured into the reaction tank using a metering pump at a flow rate that gave a volume ratio of liquid A:liquid B of 4.5:1, and the pH value of the reaction solution was maintained in the range of 9.3 to 9.6 with liquid C, and the reaction temperature was 40°C to generate a precipitate. After filtration and washing, the precipitate was re-emulsified in ion-exchanged water to obtain a raw material hydrotalcite slurry. The hydrotalcite in the obtained hydrotalcite slurry had a concentration of 5.6 mass%. The obtained hydrotalcite slurry was vacuum dried overnight at 40°C. NaF was dissolved in ion-exchanged water to a concentration of 100 mg / L, and a solution was prepared by adjusting the pH to 7.0 using 1 mol / L HCl or 1 mol / L NaOH, to which the dried hydrotalcite was added to a concentration of 0.1% (w / v%). The mixture was stirred at a constant speed using a magnetic stirrer for 48 hours to prevent settling. The mixture was then filtered through a membrane filter with a pore size of 0.5 μm and washed with ion-exchanged water. The obtained hydrotalcite was then dried at 40°C. The mixture was dried in a vacuum overnight and then crushed. The composition and physical properties of the resulting hydrotalcite particles 1 are shown in Table 2.

[0111] <Preparation of hydrotalcite particles 2 to 13> Except for appropriately adjusting the concentrations of the liquid A, the liquid B and the NaF aqueous solution, hydrotalcite particles 2 to 13 were obtained in the same manner as in the production example of the hydrotalcite particles 1. The compositions and physical properties of the obtained hydrotalcite particles 2 to 13 are shown in Table 2.

[0112] <Preparation of Hydrotalcite Particles 14> Hydrotalcite particles 14 were obtained in the same manner as in Production Example of Hydrotalcite Particles 1, except that ion-exchanged water was used instead of the NaF aqueous solution in Production Example of Hydrotalcite Particles 1. The composition and physical properties of the obtained hydrotalcite particles 14 are shown in Table 2. [Table 2] The average particle size is the number-average particle size Dh of the primary particles.

[0113] <Production Example of Polyester Resin A> A reaction apparatus equipped with a stirrer, a thermometer, and an outflow cooler was charged with 20 parts of propylene oxide-modified bisphenol A (2-mol adduct), 80 parts of propylene oxide-modified bisphenol A (3-mol adduct), 20 parts of terephthalic acid, 20 parts of isophthalic acid, and 0.50 parts of tetrabutoxytitanium, and an esterification reaction was carried out at 190°C. Thereafter, 1 part of trimellitic anhydride (TMA) was added, and the temperature was raised to 220°C while the pressure inside the system was gradually reduced, and a polycondensation reaction was carried out at 150 Pa to obtain polyester resin A. Polyester resin A had an acid value of 12 mgKOH / g and a softening point of 110°C.

[0114] (Preparation of Polyester Resin Particle Dispersion A) Polyester resin A: 200 parts Ion-exchanged water: 500 parts The above materials were placed in a stainless steel container, heated to 95°C in a hot bath, and melted, and then 0.1 mol / L sodium bicarbonate was added while thoroughly stirring at 7,800 rpm using a homogenizer (IKA: Ultra Turrax T50) to make the pH greater than 7.0. Thereafter, a mixed solution of 3 parts of sodium dodecylbenzenesulfonate and 297 parts of ion-exchanged water was gradually added dropwise to emulsify and disperse the mixture, thereby obtaining polyester resin particle dispersion A. The particle size distribution of this polyester resin particle dispersion A was measured using a particle size measuring device (LA-960V2, manufactured by Horiba, Ltd.), and the number average particle size of the polyester resin A particles contained therein was 0.25 μm, and no coarse particles exceeding 1 μm were observed.

[0115] (Preparation of Wax Particle Dispersion) Ion-exchanged water: 500 parts Wax (hydrocarbon wax; maximum endothermic peak temperature 77°C): 250 parts The above materials were placed in a stainless steel container, heated to 95°C in a hot bath, and melted. While thoroughly stirring at 7,800 rpm using a homogenizer (IKA Ultra Turrax T50), 0.1 mol / L sodium bicarbonate was added to adjust the pH to greater than 7.0. Thereafter, a mixed solution of 5 parts of sodium dodecylbenzenesulfonate and 245 parts of ion-exchanged water was gradually added dropwise to emulsify and disperse the wax particles. The particle size distribution of the wax particles contained in this wax particle dispersion was measured using a particle size measuring device (LA-960V2, manufactured by Horiba, Ltd.), and the number-average particle size of the wax particles contained was 0.35 μm, and no coarse particles exceeding 1 μm were observed.

[0116] (Preparation of Colorant Particle Dispersion 1) CI Pigment Blue 15:3: 100 parts Sodium dodecylbenzenesulfonate: 5 parts Ion-exchanged water: 400 parts The above was mixed and dispersed using a sand grinder mill. The particle size distribution of the colorant particles contained in this colorant particle dispersion 1 was measured using a particle size measuring device (LA-960V2, manufactured by Horiba, Ltd.), and the number-average particle size of the colorant particles contained was 0.2 μm, and no coarse particles exceeding 1 μm were observed.

[0117] <Production Example of Toner Particle 1> Polyester resin particle dispersion A: 500 parts Colorant particle dispersion 1: 50 parts Wax particle dispersion: 50 parts Sodium dodecylbenzenesulfonate: 5 parts A reactor (1-liter flask, anchor blade with baffles) was charged with polyester resin particle dispersion A, wax particle dispersion, and sodium dodecylbenzenesulfonate, and mixed uniformly. Meanwhile, colorant particle dispersion 1 was mixed uniformly in a 500-mL beaker, and this was gradually added to the reactor while stirring to obtain a mixed dispersion. 0.5 parts of aluminum sulfate aqueous solution (solid content) was added dropwise while stirring the obtained mixed dispersion to form aggregated particles. After the dropwise addition was completed, the system was replaced with nitrogen and the mixture was kept at 50°C for 1 hour and then at 55°C for another 1 hour. The temperature was then raised and kept at 90°C for 30 minutes. The temperature was then lowered to 63°C and kept at that temperature for 3 hours to form fused particles. The reaction at this time was carried out in a nitrogen atmosphere. After the specified time had elapsed, the mixture was cooled to room temperature at a rate of 0.5°C per minute. After cooling, the reaction product was subjected to solid-liquid separation in a 10 L pressure filter under a pressure of 0.4 MPa to obtain a toner cake. Thereafter, ion-exchanged water was added to the pressure filter until it was filled with water, and the toner cake was washed under a pressure of 0.4 MPa. The same washing was repeated three times in total. After that, solid-liquid separation was performed under a pressure of 0.4 MPa, followed by fluidized bed drying at 45°C to obtain a toner cake of a median volumetric value. Toner particles 1 having a diameter of 6.8 μm were obtained.

[0118] <Production Example of Toner Particle 2> (Preparation of aqueous medium) Ion-exchanged water: 1000.0 parts Sodium phosphate: 14.0 parts 10% hydrochloric acid: 4.5 parts The above materials were stirred at 12000 rpm using a TK homomixer (manufactured by Tokushu Kika Kogyo Co., Ltd.) to obtain a mixture. The obtained mixture was kept at 65°C for 60 minutes while purging with nitrogen. Next, an aqueous calcium chloride solution obtained by dissolving 8 parts of calcium chloride in 10 parts of ion-exchanged water was added to the mixture all at once to prepare an aqueous medium containing a dispersant. The pH of the prepared aqueous medium was 5.5.

[0119] (Preparation of pigment dispersion 1: pigment dispersion step) Styrene: 60.0 parts Pigment Blue 15:3: 6.0 parts Charge control agent (Orient Chemical Industries Co., Ltd.: Bontron E-88): 0.5 parts The above materials and zirconia particles with a diameter of 1.7 mm were put into an attritor (Mitsui Miike Chemical Engineering Co., Ltd.) and mixed at 220 rpm for 5 hours to disperse the colorant and charge control agent in styrene. After dispersion, the zirconia particles were separated to prepare pigment dispersion 1.

[0120] (Preparation of Polymerizable Monomer Composition 1) Styrene: 15.0 parts n-Butyl acrylate (n-BA): 25.0 parts Polyester resin A: 6.0 parts The above materials were mixed and stirred for 2 hours to dissolve the polyester resin A, and a polymerizable monomer composition 1 was obtained.

[0121] (Preparation of Polymerizable Monomer Composition 2) Pigment dispersion 1 and polymerizable monomer composition 1 were mixed, and then the following materials were added. Hydrocarbon wax (melting point: 77°C): 10.0 parts Divinylbenzene: 0.02 parts After the addition, the mixture was heated to 65° C. while being mixed. The mixture was dissolved uniformly at 65° C. for 30 minutes while being kept at 65° C. using a TK homomixer (manufactured by Tokushu Kika Kogyo Co., Ltd.) at 500 rpm to obtain a polymerizable monomer composition 2.

[0122] (granulation / polymerization process) The obtained polymerizable monomer composition 2 was put into the above-mentioned aqueous medium. Next, 10.0 parts of a polymerization initiator t-butyl peroxypivalate (25% toluene solution) was added, and the mixture was stirred at 10,000 rpm for 5 minutes at 65°C under nitrogen purge with a TK homomixer (manufactured by Tokushu Kika Kogyo Co., Ltd.), and granulated at pH 5.5. After that, the mixture was heated to 70°C while stirring with a paddle stirring blade, and reacted for 5 hours while stirring.

[0123] (Distillation process) After the polymerization reaction was completed, the temperature inside the vessel was raised to 100° C., and distillation was carried out for 4 hours.

[0124] (Washing / Drying / Classification / External Addition Process) After the distillation process was completed, the reaction vessel was cooled to 30°C at a rate of 5°C / min, and 10% hydrochloric acid was added to adjust the pH to 2, while stirring for 2 hours to dissolve the dispersant. The resulting emulsion was filtered under pressure and further washed with 2000 parts by mass or more of ion-exchanged water. The resulting cake was again washed with 100 parts by mass of ion-exchanged water. The mixture was returned to 0 parts by mass of ion-exchanged water, and 10% hydrochloric acid was added to adjust the pH to 1 or less, and the mixture was washed again while stirring for 2 hours. The emulsion obtained in the same manner as above was filtered under pressure, washed with 2000 parts by mass or more of ion-exchanged water, thoroughly aerated, dried and air-classified to obtain toner particles 2 having a volume-based median diameter of 7.0 μm.

[0125] <Production Example of Toner Particle 3> Polyester resin A: 100 parts Charge control agent (Orient Chemical Industries Co., Ltd.: Bontron E-88): 0.5 parts Hydrocarbon wax (melting point: 77°C): 10.0 parts Pigment Blue 15:3: 6.0 parts The above raw materials were premixed in a Henschel mixer FM10C (Mitsui Miike Chemical Engineering Co., Ltd.), and then kneaded using a twin-screw kneading extruder (PCM-30: manufactured by Ikegai Iron Works Co., Ltd.) set at a rotation speed of 200 rpm, with the set temperature adjusted so that the direct temperature near the outlet of the kneaded material was 155°C. The resulting molten kneaded material was cooled, and the cooled molten kneaded material was coarsely pulverized using a cutter mill. The resulting coarsely pulverized material was then finely pulverized using a turbo mill T-250 (manufactured by Turbo Kogyo Co., Ltd.) with a feed rate of 20 kg / hr and an air temperature adjusted so that the exhaust temperature was 38°C. The resulting finely pulverized material was classified using a multi-division classifier utilizing the Coanda effect, to obtain toner particles 3 having a volume-based median diameter of 7.3 μm.

[0126] <Toner 1 Manufacturing Example> Toner particles 1 (100.0 parts) obtained above, hydrotalcite particles 1 (0.200 parts) and silica particles 1 (1.50 parts) were externally added and mixed using FM10C (manufactured by Nippon Coke & Engineering Co., Ltd.) The external addition conditions were as follows: the lower blade was set to A0 blade, the distance to the deflector wall was set to 20 mm, the amount of toner particles charged was 2.0 kg, and the rotation speed was 66.6 s. -1 The external addition time was 10 minutes, and the cooling water temperature was 20°C and the flow rate was 10 L / min. Thereafter, the mixture was sieved through a mesh having an opening of 200 μm to obtain toner 1. The physical properties of the obtained toner 1 are shown in Table 3.

[0127] <Production Examples of Toners 2 to 42> Toners 2 to 42 were obtained in the same manner as in the production example of toner 1, except that the toner particles, hydrotalcite particles, and silica particles were changed as shown in Table 3. The physical properties of toners 2 to 42 obtained are shown in Table 3. [Table 3] Regarding "Mg / Al", "F / Al", "D / Q", "D / (SQ)", "M / S", and "roundness of silica particles" measured by the above-mentioned method using each of the above toners 1 to 42, The results or values ​​were the same as those of the analysis of the hydrotalcite particles or silica particles used alone. In addition, in toners 1 to 33, 35, 36 and 38 to 42, the line analysis by STEM-EDS mapping analysis confirmed the presence of fluorine inside the hydrotalcite particles.

[0128] <Image evaluation> The methods for evaluating each of the toners 1 to 42 are described below. The evaluation results are shown in Tables 4 and 5. The evaluation method and criteria are as follows. The image forming device used was a commercially available laser printer "LBP-9660Ci (Canon)" modified to have a process speed of 325 mm / sec. A commercially available toner cartridge (cyan) (Canon) was used as the process cartridge. The product toner was removed from the inside of the cartridge, and after cleaning with an air blower, 270 g of each toner to be evaluated was filled in. In addition, the product toner was removed from each station of yellow, magenta, and black, and the evaluation was performed by inserting yellow, magenta, and black cartridges with the toner remaining amount detection mechanism disabled.

[0129] (1) Evaluation of charge build-up The above process cartridge, the above modified laser printer, and evaluation paper (CS-068 (Canon) A4: 68g / m 2 ) was left to stand in a high temperature and high humidity environment (30°C / 80% RH, hereinafter referred to as H / H environment) for 48 hours. In the H / H environment, when the evaluation paper is viewed vertically, a horizontal band of 10 mm long all-cyan image area (with a coverage of 0.45 mg / cm2) is printed on the evaluation paper from 10 mm to 20 mm from the top of the paper. 2 ), and from there in the downstream direction there is a 10 mm long all-white image area (with a coverage of 0.00 mg / cm 2 ), and then, in the downstream direction, there is a half-tone image area with a length of 100 mm (with a coverage of 0.20 mg / cm 2 ) was output.

[0130] The charge rise performance was evaluated based on the difference (image density difference) between the image density of the portion of the halftone image area that is one revolution of the developing roller downstream from the all-cyan image area and the image density of the portion of the halftone image area that is one revolution of the developing roller downstream from the all-white image area. The image density was measured using a Macbeth Reflection Densitometer RD918 (manufactured by Macbeth) according to the attached instruction manual by measuring the relative density against the white background of the paper used, and the obtained relative density was taken as the image density value. The charge rise property was evaluated according to the following evaluation criteria. A grade of C or higher was judged to be good. When the charge rise property is good, the toner supplied onto the charging roller is quickly charged, so that the image density after the all-cyan image portion and the all-white image portion does not change, and a good image can be obtained. (Evaluation Criteria for Charge Rise Property) A: Image density difference is less than 0.03 B: Image density difference is 0.03 or more and less than 0.06 C: Image density difference is 0.06 or more and less than 0.10 D: Image density difference is 0.10 or more

[0131] (2) Durability evaluation After the evaluation of the charge rise property, 25,000 sheets of images with a print ratio of 1.0% were continuously printed on the evaluation paper in a H / H environment. After leaving it to stand in the same environment for 72 hours, the same evaluation as for the charge rise property was performed. The charge rise property was evaluated according to the above-mentioned evaluation criteria, and durability was evaluated.

[0132] (3) Evaluation of development blade adhesion In the evaluation of durability, the cartridge that had been printed 25,000 sheets in an H / H environment was removed from the printer body, and the fused material on the developing blade was visually and microscopically observed using an ultra-depth shape measuring microscope (manufactured by Keyence Corporation). Based on the evaluation images and the results of visual and microscopic observation, the evaluation was made based on the following criteria. It is known that in this durability test, the hydrotalcite particles detached from the toner form aggregates together with the spherical silica particles, and as they grow with continued use, the evaluation results decrease. A grade of C or higher was judged to be good. (Evaluation criteria for development blade adhesion) A: There are no problems with the image, and no fusion is observed under a microscope. B: No problem with the image, slight fusion observed under microscope C: Three or more thin vertical lines are visible in the halftone image. D: Three or more vertical white lines are seen on the solid image.

[0133] (4) Evaluation of regulatory deficiencies The evaluation of the regulation failure was performed in a low temperature and low humidity environment (15°C / 10% RH, hereinafter referred to as L / L environment) where charge-up is severe. In the L / L environment, the above process cartridge, the above modified laser printer, and the evaluation paper (CS-068 (Canon) A4: 68 g / m 2 ) was subjected to an intermittent durability test of 30,000 sheets, outputting two sheets every four seconds at a print rate of 1%. After the sheets were fed through, the toner load was 0.3 mg / cm 2 A halftone image having the above composition was printed, and the amount of spot-like streaks and toner clumps appearing on the halftone image was evaluated. (Criteria for evaluation of poor regulation) A: Not occurred B: No spot-like streaks, but a few small toner clumps C: There are some spot-like streaks on the edges or 4 or 5 small toner clumps D: There are spot-like streaks all over the surface, or there are six or more small or obvious toner clumps.

[0134] (5) Evaluation of solid color tracking ability The solid image tracking ability in an L / L environment was evaluated by the following method. In an L / L environment, the above process cartridge, the above modified laser printer, and evaluation paper (CS-068 (Canon) A4: 68 g / m 2) at a printing rate of 1%, 5,000 sheets were continuously fed per day, and then the ink was left in the printer for a day, after which the ink was evaluated for its ability to follow solid images. Three all-cyan images were output in succession as sample images, and the solid-color tracking performance of the third all-cyan image obtained was evaluated by visual inspection. The evaluation criteria are as follows. It is known that the higher the fluidity of the toner, the better the results for the above evaluation items. The evaluation was performed after 15,000 sheets were passed through. (Evaluation criteria for solid color conformity) A: Image density is uniform and not uneven. B: There is slight unevenness in image density. C: Image density is uneven, but not problematic D: The image density is uneven and the image is not uniform.

[0135] [Examples 1 to 33] In Examples 1 to 33, the above evaluations were carried out using toners 1 to 33, respectively. Incidentally, Example 28 was evaluated as a reference example. The evaluation results are shown in Table 4.

[0136] [Comparative Examples 1 to 9] In Comparative Examples 1 to 9, the above evaluation was carried out using toners 34 to 42, respectively. The evaluation results are shown in Table 5. [Table 4]

[0137] [Table 5]

[0138] Good results were obtained in all the evaluation items in Examples 1 to 33. On the other hand, in Comparative Examples 1 to 9, results were inferior to those of the Examples in any of the above evaluation items. As a result of the above, according to the present disclosure, it is possible to provide a toner that achieves high levels of chargeability, developability, and fluidity throughout durable use, regardless of the usage environment.

[0139] The present disclosure relates to the following configurations. (Configuration 1) A toner having toner particles and an external additive, The external additive contains silica particles and hydrotalcite particles, In a line analysis in a STEM-EDS mapping analysis of the toner, fluorine is present inside the hydrotalcite particles, When the content of the hydrotalcite particles with respect to 100 parts by mass of the toner particles is defined as Wh, the Wh is 0.040 to 1.000 parts by mass, When the content of the silica particles with respect to 100 parts by mass of the toner particles is designated as Ws, Ws is 0.08 to 6.00 parts by mass, The solid of the silica particles 29 When the sum of the areas of the peaks of M units, D units, T units, and Q units present in the chemical shift range of −140 to 100 ppm obtained by Si-NMR DD / MAS method is S, the area of ​​the peak of the D unit present in the range of −25 to −15 ppm is D, and the area of ​​the peak of the Q unit present in the range of −130 to −85 ppm is Q, The Wh, the Ws, the S, the D and the Q satisfy the following formulas (1) to (3): A toner characterized by: 0.05≦D / Q≦0.50 (1) 0.95≦D / (SQ)≦1.00 (2) 0.4≦Ws / Wh≦20.0 (3) (Configuration 2) 2. The toner according to claim 1, wherein the hydrotalcite particles contain magnesium and aluminum. (Configuration 3) The toner according to configuration 2, wherein the ratio Mg / Al of the atomic concentration of magnesium to aluminum in the hydrotalcite particles, which is obtained from main component mapping of the hydrotalcite particles by STEM-EDS mapping analysis of the toner, is 1.5 to 4.0. Toner. (Configuration 4) The hydrotalcite particles contain aluminum, The toner according to any one of configurations 1 to 3, wherein a value F / Al of a ratio of atomic concentration of fluorine to aluminum in the hydrotalcite particles, obtained from main component mapping of the hydrotalcite particles by STEM-EDS mapping analysis of the toner, is 0.02 to 0.60. (Configuration 5) The solid of the silica particles 29 The toner according to any one of configurations 1 to 4, wherein M / S is 0.010 or less, where M is the area of ​​a peak of M units having a peak top in the range of 10 to 25 ppm of a chemical shift obtained by Si-NMR DD / MAS method. (Configuration 6) The number average particle diameter Dh of the primary particles of the hydrotalcite particles is 60 to 1000 nm; The number average particle size Ds of the primary particles of the silica particles is 5 to 100 nm; 6. The toner according to any one of configurations 1 to 5, wherein the ratio of Dh to Ds, Dh / Ds, is from 5.0 to 200.0. (Configuration 7) 7. The toner according to any one of configurations 1 to 6, wherein the circularity of the silica particles is less than 0.80. (Configuration 8) The toner according to any one of configurations 1 to 7, wherein the silica particles are silicone oil-treated silica particles.

Claims

1. A toner having toner particles and an external additive, The external additive contains silica particles and hydrotalcite particles, In a line analysis in a STEM-EDS mapping analysis of the toner, fluorine is present inside the hydrotalcite particles, The hydrotalcite particles contain magnesium and aluminum, a ratio value F / Al of the atomic concentration of fluorine to aluminum in the hydrotalcite particles, which is obtained from main component mapping of the hydrotalcite particles by STEM-EDS mapping analysis of the toner, is 0.02 to 0.60; When the content of the hydrotalcite particles with respect to 100 parts by mass of the toner particles is Wh, Wh is 0.040 to 1.000 parts by mass, When the content of the silica particles relative to 100 parts by mass of the toner particles is designated as Ws, Ws is 0.08 to 6.00 parts by mass, The solid of the silica particles 29 When the sum of the areas of the peaks of M units, D units, T units, and Q units present in the chemical shift range of −140 to 100 ppm obtained by Si-NMR DD / MAS method is S, the area of ​​the peak of the D unit having a peak top in the range of −25 to −15 ppm is D, and the area of ​​the peak of the Q unit having a peak top in the range of −130 to −85 ppm is Q, The Wh, the Ws, the S, the D and the Q satisfy the following formulas (1) to (3), 0.05≦D / Q≦0.50 (1) 0.95≦D / (S-Q)≦1.00...(2) 0.4≦Ws / Wh≦20.0 (3) a ratio Mg / Al of the atomic concentration of magnesium to aluminum in the hydrotalcite particles, which is obtained from main component mapping of the hydrotalcite particles by STEM-EDS mapping analysis of the toner, is 1.5 to 4.0; A toner characterized by:

2. The solid of the silica particles 29 2. The toner according to claim 1, wherein M / S is 0.010 or less, when M is the area of ​​a peak of M units having a peak top in the range of 10 to 25 ppm in a chemical shift obtained by Si-NMR DD / MAS method.

3. The number average particle diameter Dh of the primary particles of the hydrotalcite particles is 60 to 1000 nm; The number average particle size Ds of the primary particles of the silica particles is 5 to 100 nm; The ratio of Dh to Ds, Dh / Ds, is 5.0 to 200.0; The toner according to claim 1 or 2.

4. 3. The toner according to claim 1, wherein the circularity of the silica particles is less than 0.

80.

5. 3. The toner according to claim 1, wherein the silica particles are silicone oil-treated silica particles.

Citation Information

Patent Citations

  • Toner and image forming method

    JP2000035692A

  • Image forming device

    JP2002221820A

  • Layered double hydroxide and composition containing the same

    JP2005272323A

  • Electrophotographic color toner

    JP2009042343A

  • Toner

    JP2019045578A